2022
DOI: 10.1101/2022.08.09.503399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human iPSC Derived Enamel Organoid Guided by Single-Cell Atlas of Human Tooth Development

Abstract: Tooth enamel secreted by ameloblasts is the hardest material in the human body, acting as a shield protecting the teeth. However, the enamel is gradually damaged or partially lost in over 90% of adults and cannot be regenerated due to a lack of ameloblasts in erupted teeth. Here we use sci-RNA-seq to establish a spatiotemporal single-cell atlas for the developing human tooth and identify regulatory mechanisms controlling the differentiation process of human ameloblasts. We reveal key signaling pathways involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…These dental epithelial cells differentiated from hiPSCs, when co-cultured with human dental pulp stem cells (Kim et al, 2020), or recombined with the mouse dental mesenchyme (Kim et al, 2019;Kim et al, 2020;Kim et al, 2021), possessed not only osteogenic but also tooth formation capabilities and formed tooth-like structures. Furthermore, in recent studies, dental organoids were differentiated from the dental follicle isolated from unerupted wisdom teeth (Hemeryck et al, 2022), human dental pulp stem cell derived from the mesenchymal cell (Jeong et al, 2020), and enamel spheroids derived from hiPSCs (Alghadeer et al, 2022). However, the protocol for the differentiation of the dental epithelial organoid from hiPSCs has not been established yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dental epithelial cells differentiated from hiPSCs, when co-cultured with human dental pulp stem cells (Kim et al, 2020), or recombined with the mouse dental mesenchyme (Kim et al, 2019;Kim et al, 2020;Kim et al, 2021), possessed not only osteogenic but also tooth formation capabilities and formed tooth-like structures. Furthermore, in recent studies, dental organoids were differentiated from the dental follicle isolated from unerupted wisdom teeth (Hemeryck et al, 2022), human dental pulp stem cell derived from the mesenchymal cell (Jeong et al, 2020), and enamel spheroids derived from hiPSCs (Alghadeer et al, 2022). However, the protocol for the differentiation of the dental epithelial organoid from hiPSCs has not been established yet.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the two-dimensional (2D) culture system, hiPSCderived ameloblast organoids (hAOs) based on 3D culture systems have not been reported. Attempts have been made to differentiate dental organoids using human dental follicle tissues, isolated from unerupted wisdom teeth (Hemeryck et al, 2022), in addition to deriving human dental pulp stem cells from mesenchymal cells (Jeong et al, 2020) and enamel spheroids from hiPSCs (Alghadeer et al, 2022). These studies developed a long-term expandable stemness organoid model from a human tooth, replicating molecular and functional features of the originating epithelial stem cell compartment.…”
Section: Introductionmentioning
confidence: 99%
“…This study is approved by the University of Washington Institutional Review Board (IRB) for the use of human fetal tissues in both the Birth Defects Research Laboratory (CR000000131) and the Ruohola-Baker Laboratory (STUDY00005235). Tissue was collected and dissected as described in Alghadeer et al ( 47 ). Briefly, tissues from 12 to 22 weeks’ gestation were acquired from the University of Washington’s Birth Defects Research Laboratory within 6 h of initial dissection.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple signaling pathways are active throughout tooth development including fibroblast growth factor (FGF), bone morphogenic protein (BMP), hedgehog (HH), and wingless/ integrated (WNT) (7,8). Recently, single cell analysis of the developing human oral cavity revealed that transforming growth factor beta (TGFβ), neurotrophin (NT), HH, BMP, and WNT play critical roles in ameloblast development (9). However, the specific cells of the dental pulp involved in these signaling interactions and their impact on ameloblast development remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Human OB differentiation and maturation remains largely unknown due to the rarity of fetal tissue samples. Importantly, the recent single cell sequencing of the developing human OB lineage (9) now licenses a deeper understanding of OB differentiation towards regenerative dentistry.…”
Section: Introductionmentioning
confidence: 99%